Learning Media Development Flipbook Digital in Biotechnology Material in Class IX SMP Subject of Science - Pribadi, Aqila Viani; Ulfa, Saida; Fikri, Aulia (Proceedings Series of Educational Studies, 2024)
Technological developments are currently experiencing quite significant developments, including in the field of education. The results of a field survey using the interview method carried out at SMPN 3 Lawang explained that there are various forms of media used in learning activities. However, the role of this media is only conventional, such as worksheets and the use of printed books. The purpose of this writing is to develop and analyze learning media flipbook digital on biotechnology material in the science subject Class IX SMP. The method in this research uses RND (Research and Development) using the Sadiman model. The results obtained are products developed by researchers is flipbook digital on biotechnology material. Products that have been validated by material experts (98%), media experts (97%), individual trials (84%), small group tests (88%), and large group tests (90%), completeness of learning outcomes (87 %) so that it can be concluded as a media product flipbook digital biotechnology. Keywords: biotechnology; flipbook digital; instructional Media; technology